Outdoor thermal comfort conditions during summer in a cold semi-arid climate. A transversal field survey in Central Anatolia (Turkey). (15th January 2019) - Canan, Fatih; Golasi, Iacopo; Ciancio, Virgilio; Coppi, Massimo; Salata, Ferdinando
Abstract: In the present study the outdoor thermal comfort conditions in Konya (Central Anatolia, Turkey) were examined during summer. This is why a transversal field survey was carried out and over 300 questionnaires were filled by randomly chosen participants. Moreover, environmental variables as air temperature, wind speed, relative humidity and globe temperature were constantly measured. This allowed to relate the thermal perception and preference votes given by the interviewees to the morphological and furniture characteristics of the surveyed sites. Then, taking into account at the same time all the obtained data, a regression line between the thermal perception votes and the corresponding PET (Physiological Equivalent Temperature) values was obtained and a neutral PET value of 26.8 °C was calculated. Based on a logistic curve model with the probit function, a preferred PET value of 19.2 °C was determined. On the other hand, the PET comfort range of (21.6)–(32.0) °C was obtained by considering, as thermal comfort interval, the range (−0.5)-(+0.5) of the ASHRAE 7-point scale. Finally, two outdoor thermal comfort indexes were introduced. The first one, called Turkish Outdoor Comfort Index (TOCI), is able to predict the thermal perception of the considered population in hot conditions. In the second case, the Predicted Percentage of Dissatisfied (PPD) relation was modified based on the surveyed data and outdoor sites. Highlights: A survey (315 questionnaires) was carried out in central Anatolia during summer. The neutral and preferred PET values are 26.8 and 19.2 °C respectively. The PET comfort range is characterized by values ranging from 21.6 °C to 32.0 °C. The Turkish Outdoor Comfort Index (TOCI) is introduced for the hot season. The Predicted Percentage of Dissatisfied (PPD) relation is modified.